Analysis Determinant of Optimization Assets With Asset Control Intervening Variabels (Case Study at The Bogor Agricultural Technology Research and Development Center - Renea Shinta Aminda; Indupurnahayu Indupurnahayu; Soejarwati Soejarwati; Eka Yulia Ningsih (Manajemen Bisnis, 2021)
This study aims to determine how much influence the use and security of assets have on asset optimization through asset control intervening variables, this is motivated by the implementation of asset administration, management and control. The research method used is the Kolmogorof-Smirnov one sample data normality test, collinearity test, multicollinearity test, and table f analysis test, as well as analysis test using intervening variables or path analysis. Based on the results of the calculations on the data normality test, it can be concluded that the data is normally distributed, the research variables are perfectly correlated, the variable does not occur multicollinearity, the f table test can explain all independent variables, can explain the dependent variable of each variable, the variable has a direct influence through intervening variable on asset optimization. The object of research is to immediately carry out administration, management and control based on the applicable money laws and regulations and complete a complete and detailed list of assets per each asset and can also carry out control by taking inventory, asset control card and complete a list of assets in each room, prequires commitment from the leadership in the work unit in order to administer assets to improve asset optimization and training, workshops, seminars and courses are needed for asset officers at the Center for the Study and Development of Agricultural Technology